Strontium Isopropoxide: A Highly Active Catalyst for the Ring‐Opening Polymerization of Lactide and Various Lactones. Issue 20 (18th October 2019) - Bandelli, Damiano; Weber, Christine; Schubert, Ulrich S.
Abstract : Front Cover : In article number1900306, Ulrich S. Schubert and co‐workers show that Sr(OiPr)2 is a highly active catalyst/initiator for the ring‐opening polymerization of lactide and various lactones, producing polyesters with excellent end‐group fidelity. The catalyst is promising for applications in implant production because strontium is beneficial for bone regeneration.